Collagenous matrix supported by a 3D-printed scaffold for osteogenic differentiation of dental pulp cells. Issue 2 (February 2018) - Fahimipour, Farahnaz; Dashtimoghadam, Erfan; Rasoulianboroujeni, Morteza; Yazdimamaghani, Mostafa; Khoshroo, Kimia; Tahriri, Mohammadreza; Yadegari, Amir; Gonzalez, Jose A.; Vashaee, Daryoosh; Lobner, Douglas C.; Jafarzadeh Kashi, Tahereh S.; Tayebi, Lobat
Graphical abstract: Highlights: A bone extracellular-mimetic platform for osteogenic differentiation of DPCs was designed. A combinatorial scaffold fabrication approach based on 3D-printing technique and freeze-drying method was employed. The fabricated 3D-printed β-TCP/Collagen hybrid constructs showed great promise to harness DPSCs capacity toward craniomaxillofacial bone regeneration. Abstract: Objective: A systematic characterization of hybrid scaffolds, fabricated based on combinatorial additive manufacturing technique and freeze-drying method, is presented as a new platform for osteoblastic differentiation of dental pulp cells (DPCs). Methods: The scaffolds were consisted of a collagenous matrix embedded in a 3D-printed beta-tricalcium phosphate (β-TCP) as the mineral phase. The developed construct design was intended to achieve mechanical robustness owing to 3D-printed β-TCP scaffold, and biologically active 3D cell culture matrix pertaining to the Collagen extracellular matrix. The β-TCP precursor formulations were investigated for their flow-ability at various temperatures, which optimized for fabrication of 3D printed scaffolds with interconnected porosity. The hybrid constructs were characterized by 3D laser scanning microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and compressive strength testing. Results: The in vitro characterization of scaffolds revealed that the hybrid β-TCP/Collagen constructs offer superior DPCs proliferation and alkaline phosphatase (ALP) activity compared to the 3D-printed β-TCP scaffold over three weeks. Moreover, it was found that the incorporation of TCP into the Collagen matrix improves the ALP activity. Significance: The presented results converge to suggest the developed 3D-printed β-TCP/Collagen hybrid constructs as a new platform for osteoblastic differentiation of DPCs for craniomaxillofacial bone regeneration.